DC gas breakdown and townsend discharge in CO₂ - Lisovskiy, V.A.; Dudin, S.V.; Platonov, P.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2020)
We report the breakdown curves and current-voltage characteristics (CVC) of the Townsend mode DC discharge we have measured in carbon dioxide. We compare the breakdown curves measured with two different techniques. With the first technique we regard as breakdown voltage the maximum voltage which we can apply across the electrodes without igniting the discharge with fixed values of the inter-electrode distance and the gas pressure. With the second technique we register the CVC of the Townsend mode in the μA-mA range and then extrapolate them to zero current. We reveal that in the nA-μA range the CVCs of the Townsend mode may have a complicated behavior due to the formation of the space charge. Therefore the second technique furnishes incorrect values of the breakdown voltage. Виміряні криві запалювання і вольт-амперні характеристики (ВАХ) таунсендівського режиму DC розряду у вуглекислому газі. Порівнюються криві запалювання, отримані двома різними методами. У першому методі за пробійну вважається максимальна напруга, яку при фіксованих значеннях відстані між електродами і тиску газу можливо без запалювання розряду прикласти до електродів. У другому методі вимірюються ВАХ таунсендівського режиму в мкA-мA діапазоні і потім екстраполюються на нульовий струм. Показано, що в діапазоні нA-мкA через формування просторового заряду ВАХ таунсендівського режиму можуть мати складну поведінку. Тому другий метод дає некоректні значення пробійної напруги. Измерены кривые зажигания и вольт-амперные характеристики (ВАХ) таунсендовского режима DC разряда в углекислом газе. Сравниваются кривые зажигания, полученные двумя различными методами. В первом методе за пробойное принимается максимальное напряжение, которое при фиксированных значениях расстояния между электродами и давления газа можно без зажигания разряда приложить к электродам. Во втором методе измеряются ВАХ таунсендовского режима в мкмA-мA диапазоне и затем экстраполируются на нулевой ток. Показано, что в диапазоне нA-мкA из-за формирования пространственного заряда ВАХ таунсендовского режима могут иметь сложное поведение. Поэтому второй метод дает некорректные значения пробойного напряжения.